Handbook of social justice in the global south - Deb, Nikhil; Nair, Manjusha; Muschert, Glenn W. (Edward Elgar, 2025)
"This timely Handbook explores social justice in the Global South in an era of planetary crisis and shifting global dynamics. Presenting the Global South as a space of belonging and resistance to the hegemony of global capitalism, it identifies how to reimagine transformative futures for a just world. Adopting an interdisciplinary perspective, expert contributors examine the many dimensions of justice. They investigate the disparate impacts of injustices on marginalized groups across the Global South, highlighting the major shortcomings of conventional development models based around global mass consumption. The Handbook also covers the role of ecological considerations, localized struggles, resistance movements and the broader geopolitical landscape in shaping narratives of social justice. Drawing on inclusionary practices to create a balanced relationship in global knowledge production, it gives voice to scholars based in the Global South as well as those who have created a third space in the Global North. The Handbook of Social Justice in the Global South is an essential resource for students and scholars of development studies, social justice, and inequality. Policymakers will also find it invaluable for enhancing their understanding of the conditions needed for global justice"--